Escape from planet Earth - Brunker, Cal; Fraser, Brendan, 1968-; Corddry, Rob; Alba, Jessica, 1981- (Beverly Hills, CA : Anchor Bay Entertainment, 2013)
On planet Baab Scorch Supernova is a national hero who has the help of his nerdy brother, Gary.
Bonus Blu-ray contains a high definition version of the film; bonus DVD contains a standard definition version of the film.
Features: digital copy, UltraViolet enabled digital copy.
Voices: Brendan Fraser, Rob Corddry, Jessica Alba, Rick Gervais, Jonathan Morgan Heit.
MPAA rating: PG.
Blu-ray disc.
In English with optional Spanish subtitles.
Keywords: Extraterrestrial beings -- Drama; Brothers -- Drama; Action and adventure films; Computer animation films; Fiction films; Video recordings for the hearing impaired; Feature films; Animated films; Comedy films